Book review: Crossing borders, writing texts, being evaluated: cultural and disciplinary norms in academic writing by Anne Golden, Lars Anders Kulbrandstad and Lawrence Zhang - Xiao, Yuehai (Mike); He, Jingyi; Sun, Li (Frontiers in Psychology, 2024)
In the context of globalization, the demand for English academic writing instruction at the higher education level is experiencing exponential growth. Consequently, it is crucial to conduct research that transcends national, cultural, and disciplinary boundaries in order to address this pressing need. However, there is a scarcity of research examining the intricate and diverse nature of English academic writing instruction across a wide array of national, cultural, and disciplinary contexts, highlighting an area that calls for further investigation. In response to this gap, Anne Golden, Lars Anders Kulbrandstad, and Lawrence Jun Zhang have collaborated as editors on a comprehensive volume titled “Crossing Borders, Writing Texts, Being Evaluated: Cultural and Disciplinary Norms in Academic Writing.” This collection aims to inform educators and researchers about the challenges encountered in multilingual contexts of academic writing and propose empirically substantiated solutions and coping strategies. This article provides a summary of each chapter of the volume, highlights notable features, and offers constructive criticism by identifying areas for improvement. Overall, the authors’ adeptness in unraveling the complexity and diversity of English academic writing instruction permeates the entire book. Their utilization of empirical studies, insightful findings, practical recommendations, and consideration of diverse contexts all enable their contributions to the field of English academic writing instruction. Consequently, this book serves as an indispensable resource for researchers, educators, and graduate students who seek guidance in navigating the intricacies of teaching and learning academic writing in multilingual contexts.